Bone tumor resection guide using three‐dimensional printing for limb salvage surgery. Issue 6 (27th September 2018) - Park, Jong Woong; Kang, Hyun Guy; Lim, Kwun Mook; Park, Dae Woo; Kim, June Hyuk; Kim, Han Soo
Abstract : Background and Objectives: The three‐dimensional (3D)‐printed bone tumor resection guide can be personalized for a specific patient and utilized for bone tumor surgery. It is noninvasive, eidetic, and easy to use. We aimed to categorize the use of the 3D‐printed guide and establish in vivo accuracy data. Methods: We retrospectively reviewed 12 patients, who underwent limb salvage surgery using the 3D‐printed guide at a single institution. To confirm the achievement of a safe bone margin, we compared the actual and planned distances between the cutting surface and tumor, which were reported in the final pathological report and measured from the same virtual cutting plane using graphical data of the cutting guide design, respectively. Results: The use of the 3D‐printed guide was categorized as follows: (a) wide excision only, (b) wide excision and biological reconstruction with a structural bone allograft shaped in accordance with the 3D‐printed guide, and (c) wide excision and reconstruction with a 3D‐printed personalized implant. The maximal cutting error was 3 mm. Conclusions: The 3D‐printed resection guide is easy to use and shows promise in the field of orthopedic oncology, with its application in bone tumor resection and reconstruction with a structural bone allograft or 3D‐printed implant.